1995
DOI: 10.1104/pp.107.2.341
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum-Induced Genes (Induction by Toxic Metals, Low Calcium, and Wounding and Pattern of Expression in Root Tips)

Abstract: We have investigated the response of four AI-induced genes (walil, -3, -4, and -5) from wheat (Triticum aestivum L.) to other stresses. The relative transcript levels of walil (encoding a plant metallothionein-like protein), wali3 and wali5 (putative BowmanBirk proteinase inhibitors), and wali4 (phenylalanine ammoniaiyase) increased in root tips of wheat after 2-d treatments with toxic levels of ali other metals tested (Cd, Fe, Zn, Cu, Ca, In, and La). l h e expression levels of walil, -3, -4, and -5 also incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
84
1
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(89 citation statements)
references
References 18 publications
3
84
1
1
Order By: Relevance
“…We subsequently found that root growth was a more sensitive indicator of copper tolerance than fresh weight increase (Murphy and Taiz, 1996). These results are consistent with the finding that the walil MT homolog RNA message in wheat is localized in root tips (Snowden et al, 1995) and suggest that the root tip is an important site of MT2/ copper binding. Although MTs are clearly not abundant proteins, the recovery of MT1 and MT2 from copper-treated plants was 22 times higher in root tips than in basal root tissues and 6 times higher than in leaves (see Table I).…”
Section: Discussionsupporting
confidence: 79%
“…We subsequently found that root growth was a more sensitive indicator of copper tolerance than fresh weight increase (Murphy and Taiz, 1996). These results are consistent with the finding that the walil MT homolog RNA message in wheat is localized in root tips (Snowden et al, 1995) and suggest that the root tip is an important site of MT2/ copper binding. Although MTs are clearly not abundant proteins, the recovery of MT1 and MT2 from copper-treated plants was 22 times higher in root tips than in basal root tissues and 6 times higher than in leaves (see Table I).…”
Section: Discussionsupporting
confidence: 79%
“…At this point, it may be premature to speculate whether any of the wali genes might encode our 51-kD proteins; however, the fact that the wali genes are expressed in both resistant and sensitive genotypes argues against this point. Snowden et al (1995) also demonstrated that transcript levels of walil, wali3, wali4, and wali5 increased in root tips after treatment with excess Cd, Fe, Zn, Cu, Ga, In, and La. Low levels of Ca and wounding also increased transcript levels of wali3, wali4, and wali5.…”
mentioning
confidence: 79%
“…Low levels of Ca and wounding also increased transcript levels of wali3, wali4, and wali5. Thus, Snowden et al (1995) envisioned that the wali genes might encode a series of general stress response genes. We previously reported that excess Cd and Ni were mildly effective in increasing levels of our 51-kD proteins; however, excess Cu, Mn, and Zn, along with heat shock and cold stress, were ineffective elicitors (Basu et al, 1994a).…”
mentioning
confidence: 99%
“…After three washes with water, seeds (5000 per bottle) were added to 1-L Schott bottles containing 400 mL of low-ionic-strength Ruakura medium (pH 4.3;Snowden et al, 1995). The bottles were aerated in a growth chamber under conditions of 16 h of light (190 mol m Ϫ2 s Ϫ1 ) at 22°C and 8 h of dark at 18°C.…”
Section: Methodsmentioning
confidence: 99%
“…The most highly induced genes included a metallothionein-like protein and two Bowman-Birk protease inhibitors. These genes were also induced by toxic levels of all other metals tested and by physical wounding of roots (Snowden et al, 1995). An acidic PR protein, PR-2, was found to be induced in wheat by Al, as well as by a wide range of other stresses (Cruz-Ortega and Ownby, 1993).…”
mentioning
confidence: 99%